Polarizability and aromaticity index govern AhR-mediated potencies of PAHs: A QSAR with consideration of freely dissolved concentrations. (April 2021) - Wang, Ying; Yang, Xianhai; Zhang, Songyan; Guo, Tai L.; Zhao, Bin; Du, Qiong; Chen, Jingwen
Abstract: Polycyclic aromatic hydrocarbons (PAHs) are ubiquitous environmental pollutants associated with adverse human effects including cancer, and the aryl hydrocarbon receptor (AhR) is a key ligand-activated transcription factor mediating their toxicity. However, there is presently a lack of data on AhR potencies of PAHs. Simple, transparent, interpretable and predictive quantitative structure–activity relationship (QSAR) models are helpful, especially with the consideration of freely dissolved concentrations linked to bioavailability. Here, QSAR models on AhR-mediated luciferase activity of PAHs were developed with nominal median effect concentrations ( EC 50, nom ) and freely dissolved concentration ( EC 50, free ) as endpoints, and quantum chemical and Dragon descriptors as predictor variables. Results indicated that only the EC 50, free model met the acceptable criteria of QSAR model (determination coefficient ( R 2 ) > 0.600, leave-one-out cross validation ( Q L O O 2 ) > 0.500, and external validation coefficient ( Q EXT 2 ) > 0.500), implying that it has good goodness-of-fit, robustness and external predictive power. Molecular polarizability and aromaticity index reflecting the partition behavior and intermolecular interactions can effectively predict AhR-mediated potencies of PAHs. The results highlight the necessity of adoption of the freely dissolved concentration in the QSAR modeling and more in silico models need to be further developed for different animal models ( in vivo or in vitro ). Graphical abstract: Image 1 Highlights: A simple QSAR model for AhR-mediated potencies of PAHs was developed. Considering the freely dissolved concentration for QSAR modeling is necessary. The performance of EC 50, free model is better than that of the EC 50, nom model. Molecular polarizability and aromaticity index govern the AhR potencies of PAHs.